Isolation and Molecular Characteristics of a Novel Recombinant Avian Orthoreovirus From Chickens in China - Zhang, Jun; Li, Tuofan; Wang, Weikang; Xie, Quan; Wan, Zhimin; Qin, Aijian; Ye, Jianqiang; Shao, Hongxia (Frontiers in Veterinary Science, 2021)
In recent years, the emergence of avian orthoreovirus (ARV) has caused significant losses to the poultry industry worldwide. In this study, a novel ARV isolate, designated as AHZJ19, was isolated and identified from domestic chicken with viral arthritis syndrome in China. AHZJ19 can cause typical syncytial cytopathic effect in the chicken hepatocellular carcinoma cell line, LMH. High throughput sequencing using Illumina technology revealed that the genome size of AHZJ19 is about 23,230bp which codes 12 major proteins. Phylogenetic tree analysis found that AHZJ19 was possibly originated from a recombination among Hungarian strains, North American strains, and Chinese strains based on the sequences of the 12 proteins. Notably, the σC protein of AHZJ19 shared only about 50% homology with that of the vaccine strains S1133 and 1733, which also significantly differed from other reported Chinese ARV strains. The isolation and molecular characteristics of AHZJ19 provided novel insights into the molecular epidemiology of ARV and laid the foundation for developing efficient strategies for control of ARV in China.